2023
DOI: 10.1177/22808000231159238
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Influence of carbon and graphene oxide nanoparticle on the adhesive properties of dentin bonding polymer: A SEM, EDX, FTIR study

Abstract: Objective: This study was aimed at including 2.5 wt.% of carbon nanoparticles (CNPs) and graphene oxide NPs (GNPs) in a control adhesive (CA) and then investigate the effect of this inclusion on their mechanical properties and its adhesion to root dentin. Materials and methods: Scanning electron microscopy and energy dispersive X-ray (SEM-EDX) mapping were conducted to investigate the structural features and elemental distribution of CNPs and GNPs, respectively. These NPs were further characterized by Raman sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…This phenomenon has the potential to make a substantial contribution to the antibacterial efficacy of nanoparticles [40][41][42]. Existing works in the literature have often suggested that increasing nanoparticle concentrations in adhesives may have a detrimental effect on the physical and mechanical properties of materials [21,43]. However, in the current study, it is evident that a higher concentration of ZrO 2 /Ag 3 PO 4 nanoparticles has a positive impact on the adhesive's bond strength.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This phenomenon has the potential to make a substantial contribution to the antibacterial efficacy of nanoparticles [40][41][42]. Existing works in the literature have often suggested that increasing nanoparticle concentrations in adhesives may have a detrimental effect on the physical and mechanical properties of materials [21,43]. However, in the current study, it is evident that a higher concentration of ZrO 2 /Ag 3 PO 4 nanoparticles has a positive impact on the adhesive's bond strength.…”
Section: Discussionmentioning
confidence: 55%
“…EDX spectroscopy was employed to examine the elemental distribution and composition of the ZrO 2 /Ag 3 PO 4 nanoparticles [21][22][23].…”
Section: Edx Assessmentmentioning
confidence: 99%
“…To evaluate the occurrence of bond failure, the adhesive remanent index (ARI) was utilized as a measurement tool. The assessment was carried out by employing a digital microscope (Hirox KH 7700, Tokyo, Japan) (Alsunbul et al, 2023) The ARI scoring system used in the study involved the following scale: Score 0: No adhesive remaining on tooth structure (TS).…”
Section: Thermocycling Of Specimens μTbs and Adhesive Remanent Indexmentioning
confidence: 99%